Early postoperative pancreatitis following pancreaticoduodenectomy: what is clinically relevant postoperative pancreatitis?. Issue 8 (August 2019) - Birgin, Emrullah; Reeg, Alina; Téoule, Patrick; Rahbari, Nuh N.; Post, Stefan; Reissfelder, Christoph; Rückert, Felix
Abstract: Background/objectives: Postoperative pancreatitis (POP) has recently been shown to be the cause of pancreatic fistula (POPF) following pancreaticoduodenectomy (PD). The aim of the present study was to document the perioperative outcome associated with POP and determine potential risk factors for POP. Methods: Patients undergoing PD between 2009 and 2015 were identified from the prospective data base at a single center. The previous suggested definition of POP by Connor was used. Complications were graded according to the Clavien–Dindo classification and by the grading proposed for POP. Risk factors for POP were analyzed by univariate and multivariate analysis. Results: Of 190 patients, a total of 100 patients (53%) developed POP of whom 22 (12%) and 13 (7%) had grade B and grade C complications, respectively. Elevated serum CRP-levels on postoperative day (POD) 2 and elevated serum lipase on POD 1 were associated with onset of cr-POP. Conclusion: The proposed definition of POP constitutes a valuable tool to assess a serious pancreatic-surgery associated complication. Routine serum CRP and serum lipase levels on the first two postoperative days enable sufficient discrimination of clinically relevant POP.